2016
DOI: 10.1097/md.0000000000003225
|View full text |Cite
|
Sign up to set email alerts
|

Low Expression of Mucin-4 Predicts Poor Prognosis in Patients With Clear-Cell Renal Cell Carcinoma

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Several studies have shown that EPB41L3 gene expression is altered in RCC . In addition, MUC4 was previously shown to be aberrantly expressed in ccRCC . Consistent with the present findings, Niu et al .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several studies have shown that EPB41L3 gene expression is altered in RCC . In addition, MUC4 was previously shown to be aberrantly expressed in ccRCC . Consistent with the present findings, Niu et al .…”
Section: Discussionsupporting
confidence: 92%
“…36,37 In addition, MUC4 was previously shown to be aberrantly expressed in ccRCC. 38,39 Consistent with the present findings, Niu et al found that RAP1B mRNA levels are elevated in ccRCC tissues relative to adjacent normal renal tissues. 40 Additionally, Wang et al showed that the RAP1B expression was significantly elevated in RCC tumors compared to nontumorous tissues.…”
Section: Discussionsupporting
confidence: 92%
“…In recent years, there has been a growing interest in identifying novel tumor markers not only for diagnostic purposes but also to improve the prediction of prognosis 3,4. Combining the molecular biomarkers with conventional models might provide more individualized diagnosis and treatment based on molecular characteristics of the tumor 57…”
Section: Introductionmentioning
confidence: 99%
“…However, sometimes discrepancies arise between predictions and practical clinical outcomes 4. Recent studies have revealed a number of prognostic biomarkers that are associated with different features of RCC biology, and novel models that combine conventional clinicopathological factors with molecular biomarkers have been established to allow for more a precise prediction of clinical outcomes 58. Therefore, it is of great value to seek molecular markers that will improve the individual therapeutic management and clinical outcome of patients with ccRCC.…”
Section: Introductionmentioning
confidence: 99%